Thermal characterization of hydrated eco-friendly clinkers produced from pulp and paper mill waste - Simão,L. (2018)
Abstract Industrial wastes from pulp and paper mills are potentially useful materials to use as alternative materials in clinker production. In this study, eco-friendly clinkers were obtained using only waste as feedstock. Eco-friendly clinker with different C3S and C2S contents were produced and hydrated for 7 days at 40 °C, or for 28 and 90 days at room temperature. The potentialities of these waste and the products obtained were revealed through chemical (XRF), thermal (DTA/TG) and surface area (BET) analysis. For comparison, a common ordinary Portland cement (OPC) was tested. As expected, the hydration rate of formulations presenting higher C3S content was higher, generating higher amounts of Ca(OH)2. Furthermore, the amount of Portlandite formed was lower when compared to OPC.